Efecto de la congelación en la conservación de antocianinas y fenoles en (vaccinium corymbosum l.) arándano liofilizado - Cotrina Sapaico, Alfonso Segundo (2015)
In order to develop the study for greater conservation of anthocyanins and phenolic compounds in cranberry (Vaccinium corymbosum L.) lyophilized using the freezing method (conventional at -30 ° C and quickly via immersion in liquid nitrogen); this research was conducted. The most appropriate values of process variables determined by the Folin-Ciocalteu spectrophotometric method for quantitation of phenolic compounds in which it was determined that the fresh fruit, 167.15 ± 27.11 mg was obtained. GAE / g sample, and is a better alternative conservation using liquid nitrogen as reported 141.00 ± 2.15 mg. GAE / g sample. The values of the content of total anthocyanins was obtained by the method of differential pH, which indicated that in fresh fruit, an average of 167.15 ± 27.11 (mg cyanidin 3-glucoside / 100 g) and fruit frozen with liquid nitrogen 78.32 ± 2.38, the latter being the best option for preserving freezing monomeric anthocyanins. Variables such as concentration of soluble solids in the range of 11.5 and physicochemical characterization of the fruit was obtained. Keywords: